2013
DOI: 10.3109/13880209.2013.858269
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolic profiling of normal and dysmenorrhea syndrome rats and the effects of Xiang–Fu–Si–Wu Decoction intervention

Abstract: Context: Primary dysmenorrhea (PDM), a common, clinically heterogeneous endocrine disorder affecting young women, is associated with endocrinopathy and metabolic abnormalities. The Xiang-Fu-Si-Wu Decoction (XFSWD) is a traditional Chinese medicine preparation used to treat PDM. Objective: In the current study, a plasma metabonomics method based on the ultrahigh-performance liquid chromatography-quantitative time-of-flight-mass spectrometry (UHPLC-Q-TOF-MS) system was employed to examine the mechanism of XFSWD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The formula contains numerous and diverse constituents including phthalide, alkaloids, terpene lactones, etc. The metabolomics study in animals and patients with blood stasis syndrome has given evidence that the formula prevents and benefits many disorders throughout the entire body (Liu et al, 2011a , 2013a , b , c , 2014a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…The formula contains numerous and diverse constituents including phthalide, alkaloids, terpene lactones, etc. The metabolomics study in animals and patients with blood stasis syndrome has given evidence that the formula prevents and benefits many disorders throughout the entire body (Liu et al, 2011a , 2013a , b , c , 2014a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that there was signicant changes of multiple lipid metabolites in the model of KYDS, 84,85 and renal damage was also clearly associated with changes in fatty acid metabolism, 86 phospholipid level can be used as an indicator of clinical diagnosis and it is a marker of chronic renal failure. [87][88][89][90] All of the above indicated that lipid metabolism disorders were intimately linked to kidney diseases. 91 Glycerophospholipid metabolism includes phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylglycero (PG), lysophospholipids and so on.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of these markers were significantly decreased in oxytocin-induced PD rat model. After administration of Xiang-Fu-Si-Wu decoction [ 58 ], the concentrations of lysophospholipids were restored to normal levels. This result suggests that perturbations in phospholipid metabolism were associated with PD.…”
Section: Discussionmentioning
confidence: 99%